Book commissioning and acquisition - Davies, Gill, 1945- (Routledge, 2004)
A new edition of the one and only 'must-read' for anyone training to be a successful editor. Gill Davies, whilst concentrating on the essential skills of editing, has also included other challenges which editors now face, including the demands of.